Emerging therapies and new directions in the treatment of pulmonary arterial hypertension - Kopeć, Grzegorz; Skride, Andris; Ereminiene, Egle; Simkova, Iveta; Enache, Roxana; Samarzija, Miroslav; Salobir, Barbara; Jansa, Pavel (Kardiologia polska, 2025)
Pulmonary arterial hypertension (PAH) is a severe and progressive disease with limited survival prospects under currently available therapies. Since the 2022 edition of the European Society of Cardiology and European Respiratory Society guidelines on pulmonary hypertension, substantial clinical evidence has emerged, supporting a new treatment algorithm for PAH as presented at the 7th World Symposium on Pulmonary Hypertension 2024 and the following proceeding papers. Key updates include the introduction of sotatercept as a second-line therapy leading to a revised definition of maximal medical therapy now encompassing agents from four therapeutic groups (phosphodiesterase-5 inhibitors/soluble guanylate cyclase stimulators, endothelin receptor antagonists, prostacyclin pathway agents, and sotatercept), instead of three (phosphodiesterase-5 inhibitors/soluble guanylate cyclase stimulators, endothelin receptor antagonists, prostacyclin pathway agents). Other novelties include the elimination of a distinct pathway for patients with cardiopulmonary comorbidities in favor of an individualized approach, a reduction in the initial patient assessment risk categories from three to two, and a follow-up interval shortened from 3-6 months to 3-4 months post-treatment initiation. This review presents these advancements and emphasizes the need for their widespread implementation in clinical practice. At the end, we present new opportunities and challenges in the treatment of pulmonary arterial hypertension in eight Central and Eastern European countries.
Keywords: Endothelin Receptor Antagonists; Pulmonary Arterial Hypertension; risk assessment; activin signaling inhibitors; plicní arteriální hypertenze; antagonisté endotelinového receptoru; inhibitory fosfodiesterasy 5; plicní hypertenze; Humans; Antihypertensive Agents; novel therapies; antihypertenziva; sotatercept; lidé; treatment strategy; Hypertension, Pulmonary; Phosphodiesterase 5 Inhibitors